Pelatihan Penyusunan Perangkat Pembelajaran Berbasis Strategi HPC dalam Mendukung Keterampilan Hidup Abad 21 di SD Negeri Negeri Lama, Kota Ambon - Fenanlampir, Albertus; Unmehopa, Wilhelmina; Leasa, Marleny; Batlolona, John Rafafy (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This Community Learning and Empowerment Program (PPM) has the main objective of introducing and implementing the Homogeneity Psycho Cognition (HPC) strategy for teachers and students at Negeri Lama State Elementary School. Prospective partners who act as subjects in this activity are SD Negeri Negeri Lama, Teluk Ambon Baguala District, Ambon City. Partner problems are related to the lack of efforts to train and develop 21st century life skills, namely HOTS skills in learning. So far, Mitra has found it difficult to carry out evaluations related to aspects of character and emotional intelligence. In fact, these two aspects really determine the success of students. Learning is also still teacher centered. Most teachers are not yet familiar with various learning strategies, especially HPC, which have the potential to develop life skills for students. This activity is carried out in the form of assistance for teachers in understanding various learning strategies and thematic approaches in K-13. Other activities include assisting teachers in developing or implementing practical learning for students using HPC strategies, as well as developing 21st century life skills assessment instruments.